2013
DOI: 10.1016/j.bbmt.2013.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Antigen and Lymphopenia-Driven Donor T Cells Are Differentially Diminished by Post-Transplantation Administration of Cyclophosphamide after Hematopoietic Cell Transplantation

Abstract: Administration of cyclophosphamide following transplant (Post-transplant cyclophosphamide, PTC) has shown promise in the clinic as a prophylactic agent against graft vs. host disease. An important issue with regard to recipient immune function and reconstitution after PTC is the extent to which in addition to diminution of anti-host allo-reactive donor T cells, the remainder of the non-host allo-reactive donor T cell pool may be impacted. To investigate PTC’s effects on non-host reactive donor CD8 T cells, ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 55 publications
5
58
1
Order By: Relevance
“…NRM was 15% after 1 year of follow-up. 124 Consistent with preclinical data suggesting sparing of non-alloreactive T cells, 115,125 no patients had cytomegalovirus disease; only two died from fungal infections (one had graft failure). 124 Longer follow up of expanded cohorts treated in line with the JHH protocol confirmed low rates of NRM, acute GVHD and chronic GVHD.…”
Section: Clinical Outcomessupporting
confidence: 70%
See 3 more Smart Citations
“…NRM was 15% after 1 year of follow-up. 124 Consistent with preclinical data suggesting sparing of non-alloreactive T cells, 115,125 no patients had cytomegalovirus disease; only two died from fungal infections (one had graft failure). 124 Longer follow up of expanded cohorts treated in line with the JHH protocol confirmed low rates of NRM, acute GVHD and chronic GVHD.…”
Section: Clinical Outcomessupporting
confidence: 70%
“…111,114 Parallel to the effects seen on host T cells in skin allograft models, in mouse alloBMT models, the tolerogenic effects of PTCy were exerted through elimination of alloreactive donor T cells. 115 Donor T cells exposed to host antigens on day 0 were largely depleted, whereas non-alloreactive donor T cells, which divided more slowly in a lymphopenic environment, were relatively spared. 115 However, destruction of alloreactive donor T cells was necessary but not sufficient for PTCy-induced tolerance: in mouse models of MHCmatched alloBMT in which donor CD4 + T cells promote GVHD, as well as in xenograft models, donor T REG cells were necessary to prevent lethal GVHD after PTCy treatment, 116,117 an effect consistent with the results from skin allograft models.…”
Section: Post-transplantation Cyclophosphamide Biological and Preclinmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent investigations have demonstrated that alloreactive T cells proliferating in response to antigen (that is, those responsible for GVHD and graft rejection) are much more susceptible to the effects of ptCY than memory T cells (such as those responsible for immunity to pathogens post transplant) which proliferate more slowly in response to lymphopenia. 16 Furthermore, CD4(+)CD45RA(− )Foxp3 (+hi) effector regulatory T cells express high levels of aldehyde dehydrogenase and appear to readily survive the use of high-dose CY and may contribute to the prevention of GVHD following Haplo-post-HCT-CY. 17 Based upon some of these observations, the group at Johns Hopkins University translated this approach into a clinical protocol of HaploD transplantation using a non-myeloablative conditioning regimen (pre-transplant fludarabine (150 mg/m 2 ), CY (29 mg/kg) and 2 Gy TBI, a T-replete BM graft followed by ptCY (50 mg/kg on d+3), MMF (day 4 to 35) and tacrolimus (day 4 to >50).…”
Section: Use Of Post-transplant Cy To Selectively Control Allo-reactimentioning
confidence: 99%